Cecal volvulus: A Case Report & A Literature Review - Mahruqi, Ghaitha Al; Ebrahim, Marwa Al; Aghbari, Suad Al; Kindi, Sara Al; Koliyada, Sreedharan V (International Journal of Innovative Research in Medical Science, 2019)
Cecal volvulus is a rare cause of intestinal obstruction. In this report, we present a 39 year-old patient who came with cecal volvulus, and we will discuss this very rare entity